Fugitive trail - Goddard, Elizabeth (Love inspired suspense., 2020)
A killer's out for vengeance... unless this K-9 sniffs him out first. When a plane carrying dangerous convicts crashes in the Colorado Rockies, Deputy Sierra Young and her search-and-rescue K-9, Samson, race to help--and discover they're after her! With one survivor vowing revenge, Sierra's former coworker turned PI, Bryce Elliott, is determined to protect her. But can Bryce, Sierra and Samson track down the fugitive before he succeeds in taking their lives?